P036: Digoxin immune fab treatment for digoxin and non-digoxin cardioactive steroid toxicity: a scoping review. (May 2019) - Duncan, J.; Murphy, N.; Fitzpatrick, E.; Nelson, R.; Hurley, K.
Abstract : Introduction : Cardioactive steroid poisoning occurs worldwide with the use of pharmaceutical digoxin and botanical cardiac glycosides. The wholesale price of the antidote, digoxin immune fab, has increased over 300% from 2010 to 2015. Our objective was to identify gaps in the existing literature with respect to the use of digoxin immune fab in cardioactive steroid toxicity in acute care settings.Methods : We used scoping study methodology, as described by Arksey and O'Malley, to assess the range and scope of empiric research and will report: 1) sources of cardioactive steroid toxicity in acute settings; 2) doses of digoxin immune fab used in treatment; and, 3) intervention outcomes of acute cardioactive steroid toxicity following the administration of digoxin immune fab as first or second-line therapy. We collaborated with a library scientist to devise search strategies for PubMed, CINAHL, EMBASE, CENTRAL and Toxnet. We sought unpublished literature through the Canadian Electronic Library, Proquest, and Scopus and searched reference lists of included studies. We hand searched relevant conference proceedings and applicable guidelines. Two reviewers independently reviewed titles and abstracts using predetermined criteria. Using a structured data abstraction form, two reviewers independently extracted data. All discrepancies were resolved through consensus.Results : Our search strategy yielded 3458 results. After screening titles and abstracts 384 underwent full text screening. We included 147 studies and are currently extracting data from 12 French studies and 135 English studies. To date we have extracted data from 90 case reports and case series.Conclusion : Given concerns over rising costs, our findings will shed light on the extent of the evidence for use of digoxin immune fab in acute care settings.